Chapter 1 Cultures of Contagion and Containment? The Geography of Smallpox in Britain in the Pre-vaccination Era - Davenport, Romola (Oxford University Press, 2020)
Societal responses to epidemics can vary very widely, from extreme flight flight to apparent indifference. indifference. indifference. indifference. indifference. These variations are often considered to reflect structural differences in the extent of disease exposure, or cultural differences in the tendency to fatalism. Smallpox presented a major health challenge to early modern Eurasian societies, and both types of explanation have been used to account for large-scale variations in responses to the disease in Britain, Japan and Sweden, before the widespread use of vaccination. This This chapter considers the English case. Smallpox was an endemic disease of childhood in northern England, and there is little evidence of communal efforts efforts to control it, before the rapid uptake of vaccination after 1800. In the south of England however various strategies of isolation and mass immunisation were used by parish officials to reduce transmission, and smallpox remained a relatively rare and epidemic disease there outside the major cities. There are no obvious economic or geographical factors that would explain this pattern, and therefore this chapter considers cultural explanations first, before turning to an analysis of the roles that welfare institutions and uncoordinated local responses played in generating large-scale mortality patterns.